Foreldres erfaringer med utfylling av ASQ kartleggingsskjema i forbindelse med to års konsultasjonen på helsestasjonen - en kvalitativ studie - Herigstad, Linda; Glavin, Kari (Nordisk tidsskrift for helseforskning, 2019)
Parents’ experiences of completing the ASQ tool at the two-year consultation at the Child Health Center – a qualitative study This study has investigated the user perspective of parent-based screening tools at Child Health Centers. Age & Stage Questionnaires (ASQ) are used at the two years consultation at Child Health Centers. The aim was to explore parents experience of completing the ASQ tool at two years consultation at the Child Health Center. We used qualitative research methodology with in-depth interviews with parents. The findings show that parents felt positive to fill in the ASQ form. The study also shows a large variation in how parents experienced how the tool was used at the Child Health Centre. The parents’ experiences are discussed against theory and other research in the field. The findings are also discussed in light of the purpose of implementing screening tools and results of previous studies in the field. The study concludes that there are many challenges related to the implementation of the tool in the service, and more research is needed in this area.